On the discounting of cannabis and money: Sensitivity to magnitude vs. delay. (1st July 2020) - Jarmolowicz, David P.; Reed, Derek D.; Stancato, Stefanie S.; Lemley, Shea M.; Sofis, Michael J.; Fox, Andrew; Martin, Laura E.
Highlights: Students monetary delay discounting rates did not differ based on cannabis use. Cannabis users discounted cannabis more rapidly than money. Commodity-based delay discounting differences link to magnitude sensitivity. Abstract: Background: While using most drugs of abuse is associated with higher than control rates of delay discounting, cannabis use may be the exception. As such, between-commodity differences in delay discounting (i.e., money vs. cannabis) have not been thoroughly examined. We examined these between-commodity differences using modern analytic techniques to disentangle effects of subjects' sensitivity to magnitude and delay as potential drivers of any obtained delay discounting rate differences. Method: ; Fifty-eight college students (n = 33 cannabis users, n = 25 non-users) completed a monetary delay discounting task – with the cannabis users completing the cannabis problems questionnaire as well a delay discounting of cannabis task- in an on-campus laboratory. Results: Responding between groups differed on the cannabis problems questionnaire, but not on delay discounting of monetary outcomes. Cannabis users, however, discounted cannabis at higher rates than money. Multilevel logistic regression revealed that these between-commodity delay discounting differences were due to subjects' differential sensitivity to the magnitude of these two commodities, rather than sensitivity to delay to receiving these commodities. Conclusions: Although differences in delay discounting rate were not obtained between students that did and did not use cannabis, cannabis users did discount cannabis at higher rates than they did money - suggesting considerable generality of the between commodity differences in delay discounting obtained elsewhere. The current between-commodity delay discounting differences appear to be driven by differential sensitivity to the reinforcer magnitudes presented in each task – a finding that awaits replication across other comparisons before statements about generality can be made.